LEGAL PROTECTION FOR DEBTORS IN FINANCING AGREEMENTS WITH FIDUCIARY GUARANTEES - Suryanata, Yuana; Usman, Rachmadi (International Peneliti Ekonomi, Sosial dan Teknologi, 2025)
This study aims to analyze the form of legal protection for consumers in financing agreements with fiduciary guarantees and to identify legal problems that often arise in practice. This study uses a normative legal method with a statutory and conceptual approach. The main focus of the study is to examine the legal norms contained in laws and regulations, such as the Civil Code, Law Number 42 of 1999 concerning Fiduciary Guarantees, Law Number 8 of 1999 concerning Consumer Protection, as well as OJK regulations and Constitutional Court Decision Number 18/PUU-XVII/2019. In practice, standard agreements used by business actors often place debtors in a weak position because they have no room to negotiate. One of the detrimental clauses is the unilateral execution right by creditors without a fair dispute resolution mechanism. Based on the theory of legal protection by Philipus M. Hadjon, consumer protection must be provided preventively through the prohibition of detrimental clauses and repressively through effective dispute resolution, such as BPSK and class action. This study is prescriptive, emphasizing the importance of improving regulations and law enforcement in order to create fair legal protection. The results of the study indicate that even though legal instruments are available, violations of debtor rights still often occur, so strict supervision and education for consumers are needed in order to achieve fair and transparent financing practices.